Association of HLA-DPA1, HLA-DPB1, and HLA-DQB1 Alleles With the Long-Term and Booster Immune Responses of Young Adults Vaccinated Against the Hepatitis B Virus as Neonates - Wang, Wen-Chang; Lin, Yu-Shiang; Chang, Yin-Fan; Yeh, Chih-Ching; Su, Chien-Tien; Wu, Jin-Shang; Su, Fu-Hsiung (Frontiers in Immunology, 2021)
The neonatal hepatitis B vaccination (HBVac) was implemented 35 years ago in Taiwan, but many vaccinees exhibit inadequate long-term vaccine-induced seroprotective hepatitis B surface antibody (anti-HBs) levels. We investigated the association of the human leukocyte antigen (HLA) alleles (DPA1, DPB1, DQA1, and DQB1) with the long-term immunological response to the neonatal HBVac and adolescent booster HBVac in a Taiwanese cohort. We divided 281 Han students (median age 22, age range 17–29 years) into the following groups: (1) Group A (n = 61): anti-HBs titer ≥ 10 mIU/mL at the beginning of the study; (2) Group B (n = 75): anti-HBs level > 1000 mIU/mL after the first booster; (3) Group C (n = 37): anti-HBs level < 10 mIU/mL after the first booster; and (4) Group D (n = 5): anti-HBs level < 10 mIU/mL after three boosters. DQA1, DQB1, DPA1, and DPB1 typing of the participants was performed using sequence-specific oligonucleotides. Associations of HLA alleles and haplotypes with effects on neonatal HBVac and booster HBVac were examined through logistic regression analysis and Fisher’s exact test. A false discovery rate-based measure of significance, the q-value, was used for multiple comparisons, and an association was considered significant if the corresponding q-value was < 0.1. DPA1 alleles were associated with the long-term immunological response to the neonatal HBVac. The estimated odds ratio (OR) of the lack of HBV protective immunity when carrying an additional DPA1*01 and DPA1*02 was 0.36 (95% confidence interval (CI) = 0.17–0.76, p = 0.0076) and 2.39 (95% CI = 1.17–4.87, p = 0.016), respectively. DPB1 and DQB1 alleles were associated with a response to the adolescent booster vaccination. The estimated ORs of being nonresponsive to the first booster when carrying an additional DPB1*05 and DQB1*02 were 2.11 (95% CI = 1.13–3.93, p = 0.019) and 3.73 (95% CI = 1.43–9.71, p = 0.0070), respectively. All DPB1*03 carriers responded to the first booster (p of Fisher’s exact test = 0.0045). In our study, we discovered that HLA-DPA1 was primarily associated with the long-term response of primary infantile HBVac, and HLA-DPB1 and HLA-DQB1 exhibited associations with the HBV booster vaccination.